Structural variations to a donor polymer with low energy losses. Issue 35 (21st August 2017) - Yuan, Jianyu; Ran, Niva A.; Ford, Michael J.; Wang, Ming; Ravva, Mahesh Kumar; Mai, Cheng-Kang; Liu, Xiaofeng; Brédas, Jean-Luc; Nguyen, Thuc-Quyen; Ma, Wanli; Bazan, Guillermo C.
Abstract : Two regioregular narrow bandgap conjugated polymers with a D′–A–D–A repeat unit architecture were synthesized for PSC applications. Determination of E ct in these solar cells reveals insightful changes in the energy loss relative to similar previously reported chemical structures. Abstract : Two regioregular narrow bandgap conjugated polymers with a D′–A–D–A repeat unit architecture, namely PIFCF and PSFCF, were designed and synthesized. Both polymers contain strictly organized fluorobenzo[ c ][1, 2, 5]thiadiazole (FBT) orientations and different solubilizing side chains for solution processing. Compared to the previously reported asymmetric pyridyl-[2, 1, 3]thiadiazole (PT) based regioregular polymer, namely PIPCP, PIFCF and PSFCF exhibit wider bandgaps, tighter π–π stacking, and improved hole mobilities. When incorporated into solar cells with fullerene acceptors, the E loss = E g − eV oc values of PIFCF and PSFCF devices are increased compared to solar cells based on PIPCP. Determination of E ct in these solar cells reveals that, relative to PIPCP, PIFCF solar cells lose more energy from E g − E ct, and PSFCF solar cells lose more energy from both E g − E ct and E ct − eV oc . The close structural relationship between PIPCP and PIFCF provides an excellent framework to establish molecular features that impact the relationship between E g and E ct . Theoretical calculations predict that E loss of PIFCF:PC61 BM would be higher than in the case of PIPCP:PC61 BM, due to greater E g − E ct . These findings provide insight into the design of high performance, low voltage loss photovoltaic polymeric materials with desirable optoelectronic properties.